Influence of Seed Physical Properties and Speed on the External Mechanical Damage Index and In-Row Spacing Uniformity in an Automatic Potato Planter - Mustafa Boydaş (Journal of Agricultural Sciences)
In this study, a new fully automatic potato planter was used in which the planting metering mechanism consists of cups and hold pins attached to the circumference of a vertical disc. In order to evaluate performance of the planting metering mechanism, in-row spacing uniformity and external mechanical damage index were determined (P<0.01). Also skips and doubles that caused deterioration of in-row spacing uniformity were investigated. In experiment, two potato varieties (Marfona and Agria) and two potato sizes (25-45 and 45-65 mm) were used. The ground speeds of potato planter were chosen as 3.5, 5.4 and 7.3 km h-1. The results obtained from the experiment indicated that the ground speeds and tuber physical properties significantly influenced tuber spacing accuracy and external mechanical damage index (P<0.01). While the ground speed increased, accuracy of tuber spacing decreased. The highest coefficient of variation (CV%) values were obtained from ground speed of 7.3 km h-1, Marfona variety, and tubers between 25-45 mm, with 26.80%, 25.58% and 26.27%, respectively. The highest damage index values were obtained from ground speed of 7.3 km h-1, Agria variety, and tubers between 45-65 mm, with 1.34, 1.18 and 1.23, respectively.